2017
DOI: 10.4049/jimmunol.1601001
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Repair Interacts with Autophagy To Regulate Inflammatory Responses to Pulmonary Hyperoxia

Abstract: Oxygen is supplied as supportive treatment for patients suffering from acute respiratory distress syndrome. Unfortunately, high oxygen concentration increases reactive oxygen species (ROS) generation, which causes DNA damage and ultimately cell death in the lung. Although 8-oxoguanine-DNA glycosylase (OGG-1) is involved in repairing hyperoxia-mediated DNA damage, the underlying molecular mechanism remains elusive. Here, we report that ogg-1 deficient mice exhibited a significant increase of pro-inflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…ROS generated by hyperoxia and the resulting excessive oxidative stress are important working mechanisms for lung injury [ 29,30] . Lee et al[ 31,32] found that AEC Ⅱ was the primary target cells for ROS.…”
Section: Discussionmentioning
confidence: 99%
“…ROS generated by hyperoxia and the resulting excessive oxidative stress are important working mechanisms for lung injury [ 29,30] . Lee et al[ 31,32] found that AEC Ⅱ was the primary target cells for ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Culture cells treated as above were washed with PBS twice, and prepared in ice‐cold RIPA (Thermofisher, Waltham, MA) supplemented with protease and phosphatase inhibitor cocktail (Thermofisher). Immunoblot analysis was performed and membranes were blotted with antibodies to NLRP3, AIM2, NLRC4, microtubule‐associated protein 1 light chain 3A/B (LC3A/B), caspase‐1 and β ‐actin (Cell Signaling Technology, Danvers, MA) …”
Section: Methodsmentioning
confidence: 99%
“…Triplicates were done for each sample and control. Background was corrected by using blanks containing dye alone (32).…”
Section: Nitroblue Tetrazolium Assaymentioning
confidence: 99%